The Role of the Village Government in Improving the Quality of Life of Village Communities in Sukabumi District - Nur Afandi, Muhamad; Aulia Romadona, Rizkiyana (International Journal of Educational Research & Social Sciences, 2022)
This research was conducted to understand the role of the village government in an effort to improve the quality of life of rural communities with the study area in Kebonpedes Village, Kebonpedes District, Sukabumi Regency. The analysis was conducted to determine the driving factors and inhibiting factors of the process of improving the Quality of Community Life with a case study of the village of Kebonpedes, Sukabumi Regency. The form of selecting the research location takes into account the problems and analysis of solutions that can be used. The research approach uses a qualitative approach using interviews, observation and documentation. Informants from this study were the Kebonpedes Village Government, village officials, community leaders and the Kebonpedes Village Community. in the process of analyzing using triangulation techniques. The results of the study prove that the role of the Village Government in Improving the Quality of Community Life in Kebonpedes Village has been going well, it's just that the problems that still exist are due to the limitations that exist from the analysis of the factors driving and inhibiting the role of the village government. Alternative strategies offered from the research results for the purpose of Improving the Quality of Life of the Kebonpedes Village Community, Sukabumi Regency, namely Utilizing the commitment of human resources (HR), Carrying out monitoring and evaluation activities regularly by the village government, in order to oversee the progress of efforts to improve the Quality of Life of the Kebonpedes Village Community, and Conducting socialization by making an infographic that will facilitate the process of disseminating information in rural areas in Kebonpedes village.